Population size and behavior pattern of Grus canadensis nesiotes (Aves: Gruidae) in two localities of Cuba - Ferrer-Sanchez, Yarelys (2016)
The availability of information on species abundance in the Neotropic is insufficient, and this prevents the execution of precise analysis and the definition of adequate conservation strategies for endemic and threatened species. This study aimed to analyze the population size of the endemic and threatened subspecies Grus canadensis nesiotes. For this, a simultaneous census was undertaken in 24 count stations in Isla de la Juventud (IJ) and 32 stations in Ciego de Ávila (CA), Cuba, during two consecutive days between 2008 and 2010. Abundance and behavior pattern (instantaneous method) were analyzed by habitat type, to help understand how cranes modify their behavioral pattern when the natural habitat is changed. Flocks in IJ had three individuals, and between 1.9 ± 1.5 and 2.8 ± 1.5 in CA. Population size in IJ was 164 individuals, and in CA of 137, 141 and 168 individuals for the 2008-2010 period, respectively. The counting efficacy was high (IJ: 91 %; CA: 81-87 %) and the numerical concordance was intermediate (IJ: 45.4 %; CA: 72 %). When comparing the habitat type, the abundance was higher in natural savannahs (83), followed by coastal flats (59), pines (23) and cattle pastures (7) in IJ; while in CA, marsh grasslands hosted the greatest abundance for the three years period (130; 120; 112), followed by grassland with palms (2; 17; 51) and cattle pastures (5; 4; 5). The cranes were fed more in cattle pastures and were more alert in natural savannas and marsh grasslands. The frequency of feeding and alert behaviors was different from the natural savannah/coastal flats and natural savannah/cattle pastures combinations in IJ. For CA, differences were found between marsh grasslands and marsh grasslands with palms. The population size increased by management strategies adopted in CA; nevertheless, might be affected by habitat loss associated with invasive alien plants in IJ. We propose the maintenance of prescribed fire in marsh grasslands under protection regime, as a strategy for long-term management to contribute with population growth.